The Exploration Of The Implication Of Digital Currency Adoption And Monetary Policy Effectiveness - Ntombelanga Phenicia Qithi; Sibonangaye Dick Nkalanga; Mohammed Xolile Ntshangase (CV. AFDIFAL MAJU BERKAH, 2026)
The rapid increase in digital currencies including Central Bank Digital Currencies (CBDCs) and decentralized cryptocurrencies has globally created new opportunities and challenges for monetary policy frameworks. This paper discusses the various effects of digital currency usage on the efficiency of monetary policy and analyzes the way these evolutions hamper or support the traditional transmission mechanisms of monetary policy, the change on the operational abilities of central banks, as well as the impact on financial stability. In terms of methodology, this study adopted desktop qualitative research methods. By means of a thorough review of the literature of the newest empirical and theoretical studies (2020, 2026), combined with a qualitative analysis of policy documents and case studies from the major economies, this study uncovers the most important ways through which digital currencies change the results of monetary policy. The evidence indicates that although CBDCs provide better policy transmission and financial inclusion possibilities, they at the same time bring about the risk of bank disintermediation and an increase in capital flow volatility. On the other hand, cryptocurrencies reveal the effects of these policies on effectiveness as being both positive and negative, in that an increasing use of them may lead to the weakening of traditional monetary aggregates while at the same time bringing new dimensions of financial innovation. By merging the latest findings from different fields, this paper adds a new perspective to the ongoing discussion concerning digital monetary systems. The paper also highlights the necessity of designing flexible regulatory frameworks that support innovation while also ensuring the overall stability of the system.